Assessment of the Itabira/MG population discomfort level to atmospheric pollution (Research, Society and Development, 2023)
Exposure to air pollution has negative effects on human health, affecting the quality of life and well-being of the population. Thus, this study aimed to evaluate the level of discomfort caused by atmospheric pollution (mainly by particulate matter) to the population of Itabira/MG, in order to identify the level of knowledge on the subject, associated with the socio-economic characteristics, and the perceptions about health risks. For this, an opinion survey was carried out with a sample of the population from August 29 to October 31, 2022, and was investigated the relationship, between the level of discomfort with socioeconomic characteristics, such as age group, gender, level of education and place of residence, in addition to other indicators, such as changes in lifestyle and health problems. The responses were compared with measured data on air quality at the monitoring stations closest to the respondents' neighborhood of residence. Subsequently, a cross-correlation analysis was carried out considering all the evaluated parameters and, finally, a multiple regression model was used by the stepwise method, remaining, in the end, only the most significant predictors (at the 95% level). The main factors that determined the population's level of discomfort were: age group, family income, perception of air quality in the place of residence, presence of dust and opacity in the air, frequency of house cleaning to remove dust, making changes in lifestyle and whether or not the individual is a smoker.